DIAGNOSTICS OF THE LEVEL OF COMPETENCE AND FORMATION OF SKILLS TO ANALYZE A WORK OF ART IN LITERARY READING LESSONS - X.X. Mustofoeva (International Scientific and Current Research Conferences, 2023)
Carrying out a diagnostic study of the level of formation of skills for the analysis of literary works. Based on the results obtained, determine the class with the lowest level of formation of literary text analysis skills and perform work in it aimed at the formation and development of skills to analyze works of art using effective forms and methods of work.